Peningkatan Kesadaran Siswa Melalui Program Daur Ulang Sampah Di Lingkungan Sekolah - Ediputra, Kasman; Hidayat, Adityawarman; Zulhendri, Zulhendri; Yusrina, Etika (EL-EMIR INSTITUTE, 2025)
Waste problems in school environments remain a serious challenge, impacting cleanliness, health, and environmental awareness among school communities. This community service activity aimed to enhance students’ awareness of waste management through the implementation of a recycling program at SDN 021 Bangkinang. The method used was action research with both qualitative and quantitative approaches. The subjects of this activity were 4th and 5th-grade students. The program was carried out through planning, implementation, observation, and reflection stages, involving activities such as waste sorting, training in making recycled crafts, and regular environmental education. The results of the activity showed a significant increase in students' knowledge, attitudes, and participation in waste management. A total of 87% of students were able to distinguish between organic and inorganic waste, and 80% actively participated in recycling activities. The volume of inorganic waste was reduced by up to 40% each month. This program also fostered positive habits and created a cleaner and more sustainable school environment. In conclusion, the recycling program effectively improved students’ environmental awareness and can serve as a model for environmental education at the elementary school level.